Assessing gastric cancer risk through longitudinal health check-up data: Insights from a national cohort study in South Korea - Juwon Park; Do-young Kim; Mina Suh; Yeong-Hwa Kim; Sungho Won (PLoS ONE, 2025)
Gastric cancer (GC) is the fourth most prevalent cancer and a leading cause of cancer-related fatalities in South Korea. Although periodic screening policies are in place, the early detection and prediction of GC remain challenging. This study evaluated the risk of GC incidence by utilizing longitudinal health check-up data from the National Health Insurance Service-Health Screening Cohort spanning from 2009 to 2019. The criteria selected for this study are general health examination candidates aged 40 or older who have been eligible for health insurance since 2009. The exclusion criteria included individuals diagnosed with cancer prior to 2009 or before their examination date, as well as those who did not complete the examination questionnaire. A time-dependent Cox proportional hazards model was employed to analyze the time from health examination to the first GC diagnosis, comparing our results with previous cohort studies that evaluated the GC risk through general check-up parameters. Significant risk factors for GC incidence in both genders were age, high levels of AST and γ-GTP, low levels of ALT and hemoglobin. Among males, dyslipidemia, smoking and physical activities were also significantly associated with GC risk. Although further evidence is needed, low hemoglobin levels emerged as a promising potential risk factor for GC, ascertainable through routine general health check-ups.